2020
DOI: 10.1002/pat.5009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and cytotoxic applications of curcumin‐(±) α‐lipoic acid coloaded phosphorylated chitosan nanoparticles in MDA MB 231 breast cancer cell line

Abstract: In the present work, curcumin in combination with (±) α‐Lipoic acid were used as the active agents for the preparation of phosphorylated chitosan nanoparticle. Ionic gelation method was used for the successful fabrication of the nanoparticles. Effective incorporation of the drugs in the polymeric system was revealed by Fourier‐transform infrared spectroscopy (FT‐IR) and X‐ray diffractometry (XRD). Scanning electron microscope, transmission electron microscope and dynamic light scattering method were used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 58 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…An effective reduction in proteins that promote colon cancer proliferation. Our results suggest that the siRNA-(FITC-CHC) -CMC delivery system has great potential for for RNAi therapy in diseased cells [15] .…”
Section: Targeted Therapymentioning
confidence: 76%
“…An effective reduction in proteins that promote colon cancer proliferation. Our results suggest that the siRNA-(FITC-CHC) -CMC delivery system has great potential for for RNAi therapy in diseased cells [15] .…”
Section: Targeted Therapymentioning
confidence: 76%
“…The percentage yield of freeze-dried nanoparticles was determined as described by the formula percentage yield = normalweight of the nanoparticles normalweight of .25em ( drug + polymer ) × 100 % …”
Section: Methodsmentioning
confidence: 99%
“…[56][57][58] Incorporation of phosphate functionalities in the chitin and chitosan backbone is of great interest nowadays due to their application in numerous fields such as tissue engineering, [59][60][61] flame retardants, [62][63][64] wastewater treatment, [65][66][67][68] fuel cells, 69,70 and drug delivery. 71,72 Few reviews have been reported in the literature 73,74 that summarize the different methods of phosphorylation of chitosan; however, they lack a comparative study so that the reader can choose the appropriate method. This particular review is novel in terms of the fact that, firstly, in this paper, the importance of introducing phosphorus-containing functional groups into the structure of polysaccharides (especially chitin and chitosan) is highlighted.…”
Section: An Overview Of Polymers and The Necessity Of Transitioning T...mentioning
confidence: 99%
“…5658 Incorporation of phosphate functionalities in the chitin and chitosan backbone is of great interest nowadays due to their application in numerous fields such as tissue engineering, 5961 flame retardants, 6264 wastewater treatment, 6568 fuel cells, 69,70 and drug delivery. 71,72…”
Section: Introductionmentioning
confidence: 99%